Bio-inspired tunable optics and photonics: bridging the gap between nature and technology - Do Hyeon Kim; Jeong Jin Kim; Duk-Jo Kong; Gil Ju Lee; Young Min Song (International Journal of Optomechatronics)
In the realm of optical technologies, the integration of nature’s designs and modern engineering has paved the way for groundbreaking innovations. Bio-inspired tunable optics and photonics, drawing from the intricate mechanisms found in biological systems, offer a new frontier in adaptive and efficient light management. Here, this review presents a comprehensive examination of the principles, advancements, and applications of natural light-manipulation and adaptation mechanisms, highlighting their translation into artificial tunable optics and photonic structures. Emphasizing the remarkable potential of bio-inspired systems, particularly those emulating the tunable optical functionalities of biological eyes and skins, it explores the current state of bio-inspired tunable optics and photonic devices. Our review categorizes these tunable bio-inspired systems into two foundational mechanisms: light-manipulation and light-adaptation, illustrating their wide-ranging implications from consumer electronics to next-generation technologies. This review also highlights the challenges and prospects of bio-inspired tunable optics and photonics. It emphasizes their role in promoting tunable optical properties for multifunctional devices, providing revolutionary opportunities across various sectors, including the military and everyday life, thus surpassing current cutting-edge optical technologies.